Perspectives from older adults receiving cancer treatment about the cancer-related information they receive - Margaret I Fitch; Alison McAndrew; Tamara Harth (Elsevier, 2015)
Objective: Cancer patients have reported that information plays a significant role in their capacity to cope with cancer and manage the consequences of treatment. This study was undertaken to identify the importance older adults receiving cancer treatment assign to selected types of cancer-related information, their satisfaction with the cancer-related information they received, and the barriers to effective information provision for this age group. Methods: This study was conducted in two phases with separate samples. Six hundred and eighty-four older cancer patients receiving treatment completed a standardized survey and 39 completed a semi-structured interview to gather perspectives about cancer-related information. Data were analyzed for 65-79 years and 80+ year groups. Results: Information topics about their medical condition, treatment options, and side effects of treatment were rated as most important by the older cancer patients. Women assigned a higher importance ratings than men to information overall (t = 4.8, P < 0.01). Although participants were generally satisfied with the information, they received many described challenges they experienced in communicating with health care professionals because of the medical language and fast pace of speaking used by the professionals. Conclusions: The older cancer patients in this study endorsed the same topics of cancer-related information as most important as has been reported in studies for other age groups. However, this older group recommended that, during their interactions with older individuals, health care professionals use fewer medical words, speak at a slower pace, and provide written information in addition to the actual conversation.